Proximal Contact Tightness of Direct Class II Composite Resin Restorations with Sectional Versus Circumferential Matrix Systems: A Systematic Review - Pendse, Gayatri; Misra, Rashmi; Mandke, Lalitagauri; Shah, Anuja; Khose, Ankita; Jadhav, Vasundhara (Journal of Neonatal Surgery, 2025)
Background: Achieving optimal proximal contact tightness in Class II composite resin restorations is essential to prevent food impaction, secondary caries, and periodontal complications. Matrix systems play a crucial role in shaping proximal contours, with sectional and circumferential designs being the most commonly used. However, clinical outcomes vary depending on the matrix system employed, and a systematic comparison is needed. Objective: To compare the effectiveness of sectional versus circumferential matrix systems in achieving proximal contact tightness in direct Class II composite restorations. Methods: This systematic review was conducted following PRISMA 2020 guidelines and registered in PROSPERO (CRD42024564438). A comprehensive search was performed in PubMed, Scopus, Web of Science, and the Cochrane Library. Studies comparing sectional and circumferential matrices in human or extracted teeth with quantitative measures of contact tightness were included. Risk of bias was assessed using the Cochrane RoB 2.0 tool for randomized controlled trials and a modified QUIN tool for in vitro studies. Data were synthesized narratively. Results: Nine studies were included, comprising three randomized controlled trials and six in vitro studies. Across all studies, sectional matrix systems produced significantly higher proximal contact tightness values (6.1–8.3 N) compared to circumferential systems (4.3–5.5 N). Sectional matrices also demonstrated superior anatomical adaptation and clinical satisfaction. Conclusion: Sectional matrix systems consistently outperformed circumferential matrices in achieving clinically acceptable proximal contact tightness in Class II composite restorations. Adoption of sectional matrices in clinical practice may enhance restoration quality, reduce complications, and improve patient outcomes.